Political Law of Inpatient Regulation for Patients in the Social Security Law - Seputra, Hawreyvian Rianda; Ropii, Imam (Journal of Law, Politic and Humanities, 2025)
This study aims to analyze the form of legal politics that underlies the regulation of patient hospitalization in the social security system in Indonesia, as well as the extent to which the regulation reflects the principle of social justice for all citizens. The approach used is normative juridical with descriptive-qualitative research type, which examines legal norms through literature study and analyzed based on the theory of legal politics and social justice. Data were obtained from primary legal sources such as relevant laws and regulations, as well as secondary sources in the form of scientific literature, journals, and policy documents. The results show that the regulation of patient hospitalization in Law Number 40 of 2004 concerning the National Social Security System and its derivative regulations reflects the state's efforts to ensure equal access to health services for the entire population, regardless of economic status. The solidarity-based and non-profit social security system makes hospitalization services the right of every participant, including the poor and vulnerable groups. However, implementation in the field still faces challenges in the form of limited facilities, imbalances in services between regions, and gaps in service quality between treatment classes. The Standard Inpatient Class Scheme (KRIS) that is being developed is a corrective step to realize more equitable services and reduce inequality between participants. The political law in this arrangement shows that the state does not only regulate normatively, but also seeks to realize the principle of social justice substantively through inclusive health service policies